Internal and External Governance Impact Analysis and Contribution on Operating Performance during Goods and Services Tax Implementation. A Malaysian Evidence - Sitraselvi Chandren; Mujeeb Saif Mohsen Al-Absy; Ameen Qasem (International Journal of Supply Chain Management, 2020)
The Goods Services Tax (GST) is a beneficial consumption-based tax for a country development. However, during GST implementation an adequate planning is required in the business supply chain functions and operations as to avoid any unfavourable outcome to operating performance. The GST implementation is a challenge to internal and external governance as it requires changes in the business operations. In this paper, we analyze the impact of GST to external auditors and internal control system of the Malaysian listed firms from year 2014 to 2016 using the paired t-test. We identify that the changes in audit firms and audit partners occurred during GST implementation period. Thus, no major significant impact occurred to position of external auditors and internal control system during and after GST implementation. In addition, the 200 firm-year observations regression results from year 2015 to 2016 during GST implementation reports that the external auditors to reserve independence and do not influence the relationship between internal control system with operating performance. Further, the results reveal that lower internal control system cost provides a significant improvement to firms’ short-term commitments during GST implementation.